Analisis Waktu Baku Pada Proses Pemberian Makan Maggot di UMKM Rekayasa Produk Organik (REPRO) Mijen Semarang - Aziz, Muhamad Romli; Setyaningrum, Ratih (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Garbage is a very big problem along with the increase in population. UMKM Repro Maggot is a maggot cultivation business startup that utilizes organic waste from household activities, markets and others. To get a picture of effective and efficient performance and describe the level of success that will be achieved by MSMEs in running their business, you can carry out a labor productivity analysis. Processing organic waste through maggot cultivation at UMKM Repro Maggot starts from collecting waste every day, sorting organic and inorganic waste, chopping waste into particles, fermenting waste that has been chopped for 3-7 days, pressing waste to reduce water content, providing feed (garbage). ) on BSF and compost separation. The average egg production value was 74.26 grams, and fresh maggots were 42.75 kg. Based on the results of calculating the standard time for the feeding process, it was found to be 127.36 minutes.